2014
DOI: 10.1111/1462-2920.12567
|View full text |Cite
|
Sign up to set email alerts
|

Toxin YafQ increases persister cell formation by reducing indole signalling

Abstract: Persister cells survive antibiotic and other environmental stresses by slowing metabolism. Since toxins of toxin/antitoxin (TA) systems have been postulated to be responsible for persister cell formation, we investigated the influence of toxin YafQ of the YafQ/DinJ Escherichia coli TA system on persister cell formation. Under stress, YafQ alters metabolism by cleaving transcripts with in-frame 5'-AAA-G/A-3' sites. Production of YafQ increased persister cell formation with multiple antibiotics, and by investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
126
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 93 publications
(140 citation statements)
references
References 62 publications
11
126
0
3
Order By: Relevance
“…Indole also increases the formation of antibiotic-tolerant persister cells, and the process involved is possibly linked to oxidative stress and phage shock pathways [12], which supports previous results that indole increases antibiotic resistance via multidrug transport [11,33,34]. In contrast, it has also been reported that indole decreases persister formation via phosphodiesterase DosP, which reduces cyclic adenosine monophosphate concentrations that are required to activate TnaA [35], and via the toxin protein YafQ, which cleaves TnaA mRNA [36]. The discrepancy in the role of indole and persistence is probably attributable to the different persister assay conditions used in the studies.…”
Section: Indole-3-acetonitrilesupporting
confidence: 84%
“…Indole also increases the formation of antibiotic-tolerant persister cells, and the process involved is possibly linked to oxidative stress and phage shock pathways [12], which supports previous results that indole increases antibiotic resistance via multidrug transport [11,33,34]. In contrast, it has also been reported that indole decreases persister formation via phosphodiesterase DosP, which reduces cyclic adenosine monophosphate concentrations that are required to activate TnaA [35], and via the toxin protein YafQ, which cleaves TnaA mRNA [36]. The discrepancy in the role of indole and persistence is probably attributable to the different persister assay conditions used in the studies.…”
Section: Indole-3-acetonitrilesupporting
confidence: 84%
“…Indole can inhibit N-acylated homoserine lactone-mediated quorum signaling associated with virulence and biofilm formation in Vibrio species (140). Decreases in indole concentration through changes in bacterial metabolic activity or release of factors that interfere with tryptophanase production, coincides with increased bacterial persistence and increased biofilm formation (142,143).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, indole has been reported to modulate biofilm formation in various bacteria (Lee et al 2007; Oh et al 2012; Lee et al 2015) and persister formation in E. coli (Vega et al 2012, 2013; Hu et al 2015; Kwan et al 2015). Of note, functional groups on the indole moiety control biofilm formation (Lee et al 2009), the production of virulence factors and antibiotic resistance in Pseudomonas aeruginosa (Lee et al 2009, 2012), spore maturation in Paenibacillus alvei (Kim et al 2011), and the production of immune-evasive staphyloxanthin in S. aureus (Lee et al 2013).…”
Section: Introductionmentioning
confidence: 99%